Environmental Health Risk Analysis of Particulate Matter (PM10) Exposure in Street Vendors on Bunggasi Street and Pangeran Antasari Street, Kendari City, Southeast Sulawesi, Indonesia - Oky Oktaviani Salydin; Ramadhan Tosepu; Ridwan Adi Surya; Asramid Yasin; Ranno Marlany Rachman (Journal of Health Science and Pharmacy, 2024)
Backrgound: Air pollution is a major issue in developing countries, with PM10 concentrations serving as a crucial parameter for determining air quality. PM10, which originates from the transportation, industrial, and domestic sectors, significantly contributes to air pollution. Street vendors, operating along roadsides or sidewalks near vehicle pollution sources, are at high risk of exposure to air pollutants if they remain in these environments for extended periods. Objective: This study aims to analyze the concentration of Particulate Matter (PM10), the activity patterns of street vendors, and the health risk levels (Risk Quotient, RQ) in the study area. Methods: This study employed a descriptive observational method and an Environmental Health Risk Analysis approach. Air quality measurements were conducted over two days at four measurement stations, with three measurements each day (morning, noon, and afternoon). Respondent data were collected using purposive random sampling with questionnaires. Results: The PM10 concentration measurements, adjusted to a 24-hour measurement period, revealed that Station 1 recorded 75.08 µg/m³, Station 2 recorded 73.33 µg/m³, Station 3 recorded 69.34 µg/m³, and Station 4 recorded 77.27 µg/m³. RQ analysis indicated that all 48 street vendors had RQ values ≥ 1, indicating health risks due to PM10 exposure. Risk management revealed that the safe concentration level was 0.0051 µg/m³. Exposure management at Station 4 was achieved by adjusting exposure time to 8.4 hours per day, exposure frequency to 228 days per year, and exposure duration to 5.5 years. Conclusion: The PM10 concentrations at several street vendor locations exceeded the established air quality standards. The highest exposure was found at one location, with significant health risks indicated by high RQ values. Managing exposure by regulating time, frequency, and duration of exposure was proven effective in achieving safe concentration levels. Keywords: Environmental Health Risk Analysis; Particulate Matter (PM10), Anduonohu, Indonesia